2016
DOI: 10.5539/hes.v6n4p146
|View full text |Cite
|
Sign up to set email alerts
|

ICT Teachers’ Acceptance of “Scratch” as Algorithm Visualization Software

Abstract: This study aims to investigate the acceptance of ICT teachers pertaining to the use of Scratch as an Algorithm Visualization (AV) software in terms of perceived ease of use and perceived usefulness. An embedded mixed method research design was used in the study, in which qualitative data were embedded in quantitative ones and used to explain the results. The data were collected from 214 pre-service ICT teachers studying in four large public universities. Data was gathered through a questionnaire adapted from D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 22 publications
(33 reference statements)
1
4
0
Order By: Relevance
“…The above results are in agreement with Saltan and Kara (2016) found that pre-service teachers have a positive perception and agreed that scratch is easy to use in teaching mathematics. The study conducted by Choi (2013) on Korean pre-service teachers revealed that teachers have the great intention of using scratch in future teaching.…”
Section: Boxsupporting
confidence: 91%
See 1 more Smart Citation
“…The above results are in agreement with Saltan and Kara (2016) found that pre-service teachers have a positive perception and agreed that scratch is easy to use in teaching mathematics. The study conducted by Choi (2013) on Korean pre-service teachers revealed that teachers have the great intention of using scratch in future teaching.…”
Section: Boxsupporting
confidence: 91%
“…Computer programming succeeded to boost most of the aspects of our society, respond people's needs, and being adaptable to modern and future technology (Kalelioglu & Gülbahar, 2014). Using computer programming increase the computational thinking of students (Saltan & Kara, 2016). Teachers at different levels and from different subjects use computer programming to improve teaching-learning and help students to develop skills (Ferrer-Mico, Prats-Fernàndez, & Redo-Sanchez, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…For the first step of scale development, literature related to block-based teaching programming was reviewed, available scales were examined. About acceptance or effect of Scratch as a teaching tool, there are some studies with preservice ICT teachers (Choi, 2013;Fesakis and Serafeim, 2009;Saltan and Kara, 2016); and few scale development studies with students (Kasalak and Altun, 2018). Items of scale development studies based on technology acceptance in the literature were also examined (Çam, 2012;Dönmez and Akbulut, 2019;Esen and Büyük, 2014;Özer, Eriş and Özmen, 2012;Serçemeli and Kurnaz, 2016;Teo, 2015;Turan and Haşit, 2014;Ursavaş, 2014).…”
Section: Scale Development Stepsmentioning
confidence: 99%
“…Computer programming succeeded to boost most of the aspects of our society, respond people's needs, and being adaptable to modern and future technology (Kaleliogľu & Gülbahar, 2014). Using computer programming increase the computational thinking of students (Saltan & Kara, 2016). Teachers at different levels and from different subjects use computer programming to improve teaching-learning and help students to develop skills (Ferrer-Mico et al, 2012).…”
Section: Introductionmentioning
confidence: 99%